Rescue one-stage hybrid perventricular and percutaneous device closure of multiple muscular ventricular septal defects using the new multifunctional occluder - Paul Padovani; Mohamedou Ly; Alban-Elouen Baruteau (Wolters Kluwer Medknow Publications, 2024)
Data on the safety and efficiency of perventricular device closure of complex ventricular septal defects (VSDs) are scarce. We report successful one-stage combined hybrid perventricular and percutaneous closure of the muscular VSDs in a critically ill 4-kg infant, using the new multifunctional occluder.